ASSESSMENT OF AWARENESS REGARDING PACKAGE INSERTS AMONG MEDICAL STUDENTS of a medical college at Chennai. - Dr. SHIVALI RAI; MRS SHEELA D; Dr. C B THARANI (International Journal of Pharma and Bio Sciences, 2016)
A package insert is an officially approved document provided in drug package to provide additional information about the drug. This study was conducted to assess the awareness regarding package inserts among medical students . The aim was to assess the awareness regarding package inserts among Medical students and too create awareness and to enlighten the importance of package inserts to medical students. MBBS students of Saveetha Medical College after obtaining informed consent were included in the study.Each batch was addressed about the study with prior permission of the Dean and respective HOD . This is a planed observational study using a standard questionnaire which consists of 9 questions with Yes/No format. 384 medical students took part in the study. Results expressed as percentage of total responses to that question. It was noticed that the awareness of package inserts was better among the interns. Most of them used package inserts to know the adverse effects and contraindication . From our study we conclude thata lot has to put in to make the package insert user friendly and enhance its use.Stringent rules need to be enforced to improve the quality